Implementation of government policies in small and medium industry development in Sidodadi Village Biru-Biru District Deli Serdang Regency - Mala Antika (Central Research Institute for Agriculture (CeRIA), 2023)
The research method used is field research (field research) or what is called a descriptive qualitative method, which will later describe the facts that happened, so that a conclusion can be found. The findings of this thesis are that the method for developing the opaque cracker industry in Sidodadi Village is by marketing various innovative opaque cracker products. The elements that hindered the development of the industry were insufficient capital, lack of raw materials, and previous lack of cooperation between business owners and the government, so that of the 5 (five) opaque industries that were established previously, 2 (two) of them were bankrupt. So with the incident that caused a decline in the economy in the village Sidodadi, there needs to be a government and more attention to contribute to the existing industry. And the government policy is the need for industrial owners to complete the requirements for establishing an MSME, the existence of capital assistance provided to the industry, providing marketing method training to employees in order to increasing sales, and assistance from the government and other institutions in terms of providing production equipment assistance to increase the production of opaque crackers.